The one - Morgan, Glen; Chasman, Steven; Wong, James ([Culver City, Ca] : Columbia Pictures Industries, 2001)
Sometimes, the difference between good and evil is only a matter of degrees. Officer Yulaw is on the trail of a diabolical mirror image of himself that has escaped from a parallel universe. Each time he kills his likeness he grows stronger and more powerful. Now, he is the only one standing in his way of becoming'the one.'
Executive producer, Todd Garner ; writer, Glenn Morgan, James Wong
Cast: Jet Li, Delroy Lindo, Carla Gugino
VCD format
Keywords: Heroes in motion pictures